GEOCHEMICAL FEATURES OF COPPER PORPHYRY МINERALIZATION IN THE GOSHGARCHAYORE MAGMATIC SYSTEM (MUROVDAG ORE REGION, AZERBAIJAN PART OF THE LESSER CAUCASUS) - Mansurov, М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The geochemical features of intrusive rocks and the surrounding rocks associated with porphyry copper mineralization in theGoshgarchay magmatic system were studied. Major factors of concentration of copper and copper-porphyritic mineralization in rocks of gabbro-diorite-granodiorite formation has been revealed. It has been established that the structure of this ore region was formed as a result of successive alteration of some deformation stages accompanied by development of fractures in intrusive massive, by dike intrusions, locks displacements along faults and the fractures composed of various mineral associations.Main ore components were defined and relations hips among elements were considered. Geochemical associations allowing the localization of the development area of mineralization have been analyzed in various formation stages of porphyry copper system according to the results of cluster analysis. In this study, Cu, Mo, Pb, Zn, Ag, Ni, Co, Mn, Ti, Cr, V, and Sr both in the surrounding rocks and in ore-bearing intrusive rocks were considered as stable elements. This group of elements can be regarded as indicator elements in porphyry copper.The results of the claster analysis show that the elements which are less characteristical for hydrothermal solutions (Mn, Ti, Cr, V, Sr) keep their freedom in all wallrocks and the existence of their grouping is probably associated with their transportation process from silicate rocks with surrounding basic-average content. The elements such as Cu, Mo, Ag, Pb and Zn which form free group are connected with the generation from the magmatic source in the course of crystallization differentiation process and exposure of rocks to thehydrothermal activity which is considered the source of these elements.The identification of reasons of the association of V with Cu and Zn and Pb with Fe group elements in the intrusive facies rocks is characterized with its uncertainty. The analysis of the schedule made according to the results of Cu and basic ore components (Mo, Ag, As, Bi, Gd, Co, Cr, Se, Ge, Li, Nb and etc.) in the ores of Goshgarchay deposit show their dependence on one another equally. The amount of Cu in the ores have Ag, As, Bi, Cd, Ce, Ge, Sr, Mo, Sb, Th and Ti positive correlation relationship, but it has negative correlation relationship with Co, Cr, Cs, La, Li, Pb, Rb, Ni, Nb and Zn. Direct dependence is observed for ore mass between concentrations of Cu, Mo, Pb, Zn, Ag, Se, Te and other elements in the Goshgarchay porphyry copper deposit. Three various mineral associations differing from one another participate in stock work type copper-porphyry mineralization: 1) primary sulfide minerals; 2) oxidized ores; 3) primary sulfide minerals significantly enriched with products of hydrothermal ore carrying solutions.
Keywords: copper-porphyry mineralization; Goshgarchay; geochemistry; main ore components; pointed dependence; correlation links